Hidden aspects of urban planning surface and underground development - Paul, Tim; Chow, Fiona; Kjekstad, Oddvar (Thomas Telford, 2002)
Aims to raise the awareness of geotechnical and geoenvironmental issues among urban planners and within the urban planning frameworks across Europe. Endorsed by the European Council of Town Planners, this report is useful for planners, architects and developers, and also geotechnical engineers interacting with these professions.